Antecedent and outcomes of sustainable social supply chain practices - Munira, Halili (2022)
The social pillar of sustainability is frequently overlooked in favor of the more widely discussed environmental and economic aspects. Sustainable social supply chain concept has emerged as a means of ensuring that firm operations do not hurt people or society. Despite the fact that firms have taken steps to address social issues, manufacturing companies nevertheless encounter issues including work - related accidents which pressures an urgent need to be addressed. Previous research concentrated on environmental and economic pillars but neglected to consider the social performance of ensuring that firms operate in a manner that encourages healthy and a safe working environment, protecting human rights, equity as well as ethical conduct, and philanthropy act. As a result, the study intends to create a theoretical framework that assesses social performance and determine whether stakeholder pressure influenced firms to adopt sustainable social supply chain practices. It also intends to examine the role of developing local supplier in bridging gaps of social supply chain sustainability and social performance. Quantitative method has been applied for this study. 700 survey questionnaires were sent out via an online survey to manufacturing firms registered with Federation of Malaysian Manufacturers. In total, 144 questionnaires were completed and analyzed. The questionnaires were analyzed using SmartPLS 3.2.8 software and IBM SPSS version 24. The findings show that the government and non-governmental organizations apply coercive pressure on businesses, urging firms to adopt sustainable social supply chain practices. The knowledge of institutional theory, supply chain, and operations literature has improved from these findings. Local supplier development has also been found to benefit from sustainable social supply chain practices. Furthermore, the inclusion of developing local supplier as a mediating impact in improving performance socially has contributed to the literature, and the findings show that manufacturing firms obtain better results when supply chain partners are included in the integrated ecosystem. The findings also raise awareness of sustainable social supply chain practices allowing decision-makers and industrial managers to examine the extent to which positive influences on increasing firms' social performance can be examined.